Final Approach : A Novel - Nance, John J. (New York Fawcett Crest, 1991)
Joe, a National Transportation Safety Board investigator, faces the tough job of figuring out what happened in the aviation disaster of North American Airlines Flight 255.
Keywords: Aircraft accidents -- United States. National Transportation Safety Board -- Aircraft accidents--Investigation -- Suspense fiction